Evaluation of Nutritional and Medicinal Values of Edible Wild and Cultivated Pleurotus ostreatus - Sanem Bulam; Nebahat Şule Üstün; Aysun Pekşen (Turkish Journal of Agriculture: Food Science and Technology, 2019)
Because of its high nutritional value and pharmaceutical effects, oyster mushroom (Pleurotus ostreatus (Jacq. ex Fr.) P. Kumm.) is collected from nature and cultivated in large scale. This therapeutic mushroom is consumed as a functional food or food additive in soups, cereal and dairy products, and commercially used in nutraceuticals and dietary supplements. The mycochemicals including polysaccharides (crude fiber and β-glucans), essential amino acids, ergothioneine, peptides, (glyco)proteins, lectins, phenolic compounds, polyketides (lovastatin), (tri)terpenoids, and enzymes are naturally found in the fruiting bodies and mycelial biomass of P. ostreatus. The major bioactive compounds concentration of this mushroom may be increased by modification of the substrate composition and cultivation or postharvest conditions. The goal of this review is to evaluate the results of the studies about the biochemical composition and medicinal properties of edible wild and cultivated P. ostreatus. Furthermore, the advanced novel cultivation techniques, biotechnological processes, and postharvest treatments were given in order to increase its nutritional and nutraceutical values.